2018
DOI: 10.3390/ph11010016
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin E Phosphate Nucleoside Prodrugs: A Platform for Intracellular Delivery of Monophosphorylated Nucleosides

Abstract: Vitamin E phosphate (VEP) nucleoside prodrugs are designed to bypass two mechanisms of tumor resistance to therapeutic nucleosides: nucleoside transport and kinase downregulation. Certain isoforms of vitamin E (VE) have shown activity against solid and hematologic tumors and result in chemosensitization. Because gemcitabine is one of the most common chemotherapeutics for the treatment of cancer, it was used to demonstrate the constructs utility. Four different VE isoforms were conjugated with gemcitabine at th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…Compared to gemcitabine, NUC050 is not affected by NTs inhibitors, suggesting that it can bypass NTs. Similarly, NUC050 retained most of the activity in CEM dCK(−) cells, indicating that NUC050 delivered gemcitabine-MP intracellularly [112].…”
Section: Potential Ways To Improve Gemcitabine Uptake and Efficacymentioning
confidence: 99%
“…Compared to gemcitabine, NUC050 is not affected by NTs inhibitors, suggesting that it can bypass NTs. Similarly, NUC050 retained most of the activity in CEM dCK(−) cells, indicating that NUC050 delivered gemcitabine-MP intracellularly [112].…”
Section: Potential Ways To Improve Gemcitabine Uptake and Efficacymentioning
confidence: 99%
“…The mouse xenograft model with human NCI-H460 subcutaneous implants has been shown to be robust and reproducible [ 23 ]. In this model, NUC013 administered for three consecutive days a week from study days 4 through 27 demonstrated a significant improvement in animal survival.…”
Section: Discussionmentioning
confidence: 99%
“…As per methods previously presented [ 23 ], the lipid nano-emulsion (Latitude Pharmaceuticals, San Diego, CA, USA) contained an oil phase consisting of an injectable oil and lecithin and an aqueous phase comprising a tonicity adjuster, a stabilizer, and water. The emulsions were of oil-in-water type with the mean diameter of oil droplets <100 nm.…”
Section: Methodsmentioning
confidence: 99%
“…As such, vitamin E phosphate nucleoside analogue prodrugs were envisaged to combat two mechanisms of resistance: i) downregulation of metabolic kinases (deoxycytidine kinase, dCK, in the case of 1) and ii) nucleoside transport [82,83]. Accordingly, Daifuku and co-workers synthesised and evaluated four isoforms of vitamin E conjugated to 1 (Figure 11, compounds 121-124) [84]. The in vitro GI50 of 1, vitamin E phosphate (VEP) isoforms and compounds 121-124 showed these VEP-gemcitabine prodrugs to exhibit anticancer activity, consistent with their catabolism to vitamin E and gemcitabine monophosphate.…”
Section: Vitamin E Phosphate Prodrugsmentioning
confidence: 99%
“…25, x 19 of 24Daifuku and co-workers synthesised and evaluated four isoforms of vitamin E conjugated to 1 (Figure11, compounds 121-124)[84].…”
mentioning
confidence: 99%